Cytotoxic effects of 7-geranyloxycinnamic acid isolated from Melicope lunu-ankenda (Gaertn) T.G.Hartley leaves on breast cancer cell lines (MCF-7 and MDA-MB-231 - Eliaser, Enas Mohamed Abdaallah (2022)
Breast cancer is the most prevalent form of cancer in women, it has been considered as second causing death after lung cancer, worldwide. Even though a numerous number of anticancer drugs have been applied in clinical practice worldwide, their applications are significantly limited because of its side effects. Therefore, studies have been conducted to develop new anticancer therapeutic agents with low systemic toxicity and selective toxicity to cancer cells. Melicope lunu-ankenda is widely distributed in tropical and subtropical countries including Malaysia and it is well known for its biological activities such as antibacterial, antioxidant, analgesic, antidiabetic, and antiinflammatory. A considerable number of secondary metabolites have been isolated from M. lunu ankenda like phenolic acid derivatives, flavonoids, coumarins and alkaloids. However, their underlying anticancer mechanisms of action have not been well investigated, particularly in human cell lines. Hence, the aim of the study was designed to assess the cytotoxic effects of 7-geranyloxycinnamic acid isolated from Melicope lunu-ankenda on the human breast cancer cell lines (MCF-7 and MDA-MB- 231). In this study the leaves of the plant were collected and extracted using three different solvent systems including methanol, petroleum ether and chloroform. Further extraction steps were performed to isolate the pure compound followed by 1H and 13C NMR for compound elucidation. The cytotoxic effect of the crude extracts were screened among three cancer cell lines (HT-29, HepG2 and MCF-7), the result showed that, the petroleum ether and chloroform crude extracts exhibited strong cytotoxic effect toward HT29 with IC50 20.645±0.023 μg/mL and 19.662±0.0132 μg/mL respectively, while weak cytotoxic effect by methanol crude extract on the same cancer cell lines was observed. Furthermore, moderate cytotoxic effect was recorded for the crude extracts toward HepG2 and MCF-7 cell lines respectively. On the other hand, the 7-geranyloxycinnamic acid which isolated from Melicope lunu-ankenda leaves has been tested against MCF-7, MDA-MB-231and HT-29 and it has shown a strong effect on MCF-7 and MDA-MB-231 with IC50 values 1.847±0.212 μg/mL and 1.732±0.060 μg/mL in 72 hour incubation respectively. However the compound was found to be not toxic toward MCF-10a with IC50 48.814±0.386 μg/mL at the same period of time. Both breast cancer cell lines were chosen to posses the anticancer evaluation. The compound has induced MCF-7 and MDA-MB-231 cells death with distinct characteristics evident confirmed by morphological assessment which exemplified by membrane blebbing, chromatin condensation, late apoptosis and necrosis. The ultrastructure’s alteration such as membrane blebbing, cytosolic shredding, chromatin condensation and margination, nuclear convolution, shrinkage of nuclei, and lipid droplet were observed using transmission and scanning electron microscopy. Additionally, Annexin V/PIflow cytometry assay has shown a significant increase of apoptotic features followed by modulation of caspases activities. It can be concluded that 7-geranyloxycinnamic acid is a potent anticancer agent towards MCF-7 and MDA-MB-231 cancer cell lines via modulation of apoptosis pathways. Further extensive work needed to be done to bring out the therapeutic factors and develop the potential of the compound using several animal model.